2012
DOI: 10.1128/jvi.06858-11
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Target Cells and Sequence of Infection during Experimental Infection of Ovine Fetuses with Cache Valley Virus

Abstract: Cache Valley virus-induced malformations have been previously reproduced in ovine fetuses; however, no studies have established the course of infection of cells and tissues with Cache Valley virus. To address these questions, ovine fetuses at 35 days of gestation were inoculated in utero with Cache Valley virus and euthanized at 7, 10, 14, 21, and 28 days postinfection. On postmortem examination, arthrogryposis and oligohydramnios were observed in some infected fetuses. Morphological st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Previously, we have demonstrated that fetuses infected with CVV early in gestation (ϳ35 dg) have low viral antigen and RNA signal in tissues around 56 dg and are able to clear the infection before development of an adaptive immune system at 75 dg (15). Similarly, age-based findings have been described in Akabane virus-infected fetuses (9,11,16).…”
mentioning
confidence: 68%
See 4 more Smart Citations
“…Previously, we have demonstrated that fetuses infected with CVV early in gestation (ϳ35 dg) have low viral antigen and RNA signal in tissues around 56 dg and are able to clear the infection before development of an adaptive immune system at 75 dg (15). Similarly, age-based findings have been described in Akabane virus-infected fetuses (9,11,16).…”
mentioning
confidence: 68%
“…Viral signal was also markedly reduced or absent in the ganglion, retina, kidney, and heart. CVV targets mainly cells within the CNS and MSS, and viral signal was markedly reduced in the brain and almost completely cleared in the skeletal muscle after 21 to 28 dpi in fetuses infected at 35 dg (15). Similarly, a progressive reduction in viral load, as shown by mean relative amounts of CVV RNA copies, was observed in the brain and SKM in the present study, with significant differences observed between most days of infection in the SKM, and in the brain at between 14 and 28 dpi.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations